2015
DOI: 10.1016/j.calphad.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Material design and development: From classical thermodynamics to CALPHAD and ICME approaches

Abstract: This paper presents an overview and examples of material design and development using 1) classical thermodynamics; 2) CALPHAD (CALculation of PHAse Diagrams) modeling; and 3) Integrated Computational Materials Engineering (ICME) approaches. Although the examples are given in lightweight aluminum and magnesium alloys for structural applications, the fundamental methodology and modeling principles are applicable to all materials and engineering applications. The examples in this paper have demonstrated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…There has also been much effort in recent times to apply CALPHAD and the ICME methods to develop new materials and manufacturing processes to meet design specifications . ICME combines different models (i.e., materials, manufacturing, and system design) into a holistic computational framework, as shown in Figure , where those three models can be linked to each other to predict site‐specific microstructures and properties, leading to the most efficient engineering products.…”
Section: Discussion − Identification Of Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been much effort in recent times to apply CALPHAD and the ICME methods to develop new materials and manufacturing processes to meet design specifications . ICME combines different models (i.e., materials, manufacturing, and system design) into a holistic computational framework, as shown in Figure , where those three models can be linked to each other to predict site‐specific microstructures and properties, leading to the most efficient engineering products.…”
Section: Discussion − Identification Of Opportunitiesmentioning
confidence: 99%
“…This would be an effective strategy for a wide range of other alloys and would be of great advantage to alloy development for metal AM. Additionally, CALPHAD and Integrated Computational Materials Engineering (ICME) approaches have been successfully used to predict the forming ability of metastable BMGs . Zhang et al and Hasse et al have shown thermodynamic calculations may be important in aiding the effective design of HEAs.…”
Section: Alloy Development For Metal Ammentioning
confidence: 99%
“…A variety of examples of applications are presented summarized in a number of publications [87-92]. Extensive collections of detailed examples can be found in a number of books, such as “User Applications of Alloy Phase Diagrams” [93], “User Aspects of Phase Diagrams” [94] or the two editions of “The SGTE Casebook, Thermodynamics at Work” [95].…”
Section: Applicationsmentioning
confidence: 99%
“…This allows to build the neural network with a high number of input and output parameters. Computational thermodynamics based on the CALPHAD method are widely used in materials science and are often applied for the development of new steels . It allows the calculation of phase equilibria, phase diagrams, and phase transformations as well as thermodynamic assessments in complex multi‐component alloys .…”
Section: Introductionmentioning
confidence: 99%